Improving Habits of Mind and Understanding of Wiggins Students Through Project Based Learning Model assisted by E-LKPD to Biology Learning - Bumiarti, Egina; Gloria, Ria Yulia; Roviati, Evi (International Journal of Contemporary Studies in Education, 2025)
Purpose – This study addresses the 21st-century curriculum demands by integrating digital literacy and enhancing students' habits of mind (HOM) through meaningful learning. Based on Wiggins' Understanding by Design (UbD) framework, the study aims to analyze the impact of a Project-Based Learning (PjBL) model, assisted by digital E-LKPD, on students' HOM and conceptual understanding compared to traditional teaching methods. Methodology – A quasi-experimental pretest-posttest control group design was used. Participants were purposively selected and divided into experimental and control groups. The experimental group received PjBL with digital E-LKPD, while the control group followed conventional PBL with printed LKPD. Data were collected using HOM and Wiggins-based understanding tests, student activity observations, and response questionnaires. The Mann-Whitney U test was applied for data analysis. Findings – The results showed a significant difference in the improvement of HOM and Wiggins-based understanding in the experimental group compared to the control group. Student learning activities and responses in the experimental group also met the excellent criteria. Novelty – This research uniquely integrates PjBL with digital E-LKPD to enhance thinking habits and foster deep understanding, a combination that is still rarely implemented in secondary education. Significance – The study offers valuable insights for teachers, curriculum developers, and policymakers in implementing innovative 21st-century learning strategies that combine digital tools with pedagogical approaches, fostering critical and reflective thinking.